2012
DOI: 10.1128/aac.06426-11
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Loading Dose of Colistin Methanesulfonate in Critically Ill Patients: Population Pharmacokinetics, Protein Binding, and Prediction of Bacterial Kill

Abstract: A previous pharmacokinetic study on dosing of colistin methanesulfonate (CMS) at 240 mg (3 million units [MU]) every 8 h indicated that colistin has a long half-life, resulting in insufficient concentrations for the first 12 to 48 h after initiation of treatment. A loading dose would therefore be beneficial. The aim of this study was to evaluate CMS and colistin pharmacokinetics following a 480-mg (6-MU) loading dose in critically ill patients and to explore the bacterial kill following the use of different do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
208
2
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(240 citation statements)
references
References 31 publications
16
208
2
11
Order By: Relevance
“…A loading dose of 1 g of vancomycin will fail to achieve early therapeutic levels for a significant subset of patients. In fact, loading doses of antimicrobials with low volumes of distribution (teicoplanin, vancomycin, colistin) are warranted in critically ill patients to more rapidly achieve therapeutic drug levels due to their expanded extracellular volume related to volume expansion following fluid resuscitation [148][149][150][151][152].…”
mentioning
confidence: 99%
“…A loading dose of 1 g of vancomycin will fail to achieve early therapeutic levels for a significant subset of patients. In fact, loading doses of antimicrobials with low volumes of distribution (teicoplanin, vancomycin, colistin) are warranted in critically ill patients to more rapidly achieve therapeutic drug levels due to their expanded extracellular volume related to volume expansion following fluid resuscitation [148][149][150][151][152].…”
mentioning
confidence: 99%
“…A study analyzing product data characteristics of intravenous CMS revealed a lack of uniformity between manufacturers, with quite broad variations in term of indications, dose regimens (3 to 12 MU/day), and PK (36). Moreover, dosing regimens given by manufacturers are often discordant with the dosing regimens recommended by the recent literature (21,34,41).…”
Section: Use Of Colistin In Human and Veterinary Medicine Use In Humamentioning
confidence: 99%
“…In addition, drugs with a low volume of distribution such as vancomycin and colistin, a higher loading dose is suggested [63][64][65]. For the β-lactams, it is the time when the plasma concentration of the drug should be above the pathogen minimum inhibitory concentration (MIC) level.…”
Section: Treatmentmentioning
confidence: 99%